1999
DOI: 10.1116/1.590972
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward a 30 nm silicon metal–oxide–semiconductor gate technology

Abstract: Articles you may be interested inIn-situ electron holography of surface potential response to gate voltage application in a sub-30-nm gate-length metal-oxide-semiconductor field-effect transistor Appl. Phys. Lett. 100, 143508 (2012); 10.1063/1.3700723 Technology for the fabrication of ultrashort channel metal-oxide-semiconductor field-effect transistors Fabrication of 30 nm gate length electrically variable shallow-junction metal-oxide-semiconductor field-effect transistors using a calixarene resist J. Vac. Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A high resolution is always at expense of the throughput value because reduced beam energy and resist sensitivity are required to obtain a well-defined boundary. So, it is quite challenging to simultaneously achieve high resolution and large throughput due to Tenant’s Law. , The proximity effect is weaken due to the naturally formed clear boundary, and therefore, no more exposal time is required in the developed LDW technique. Besides the super high resolution, the developed LDW technique exhibits a very attractive throughput of 10 7 μm 2 /h.…”
Section: Resultsmentioning
confidence: 99%
“…A high resolution is always at expense of the throughput value because reduced beam energy and resist sensitivity are required to obtain a well-defined boundary. So, it is quite challenging to simultaneously achieve high resolution and large throughput due to Tenant’s Law. , The proximity effect is weaken due to the naturally formed clear boundary, and therefore, no more exposal time is required in the developed LDW technique. Besides the super high resolution, the developed LDW technique exhibits a very attractive throughput of 10 7 μm 2 /h.…”
Section: Resultsmentioning
confidence: 99%
“…A more conventional MOSFET, but with a 0.1 µm amorphous silicon gate defined by an AFM tip, was fabricated by Minne et al 3 The electrical characteristics are close, but not superior, to the 64 nm gate MOSFET fabricated by EBL. 46 However, the 0.1 µm gate lithography does not seem to justify the need for SPL. Following the same paradigm but applying to a thin layer of Ti, Matsumoto et al 5 demonstrated that a SET can be fabricated by oxidizing the Ti to create a tunneling gap of 15-20 nm between the source/drain and the central conducting island.…”
Section: Devices Fabricated By Splmentioning
confidence: 99%
“…[2][3][4] SCM is an extension of contact atomic force microscopy ͑AFM͒. [2][3][4] SCM is an extension of contact atomic force microscopy ͑AFM͒.…”
Section: Introductionmentioning
confidence: 99%